2021
DOI: 10.26603/001c.29900
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Based Arm Care: The Throwers 10 Revisited

Abstract: Over the past 40 years sports medicine physicians, physical therapists and performance experts have continually worked to advance treatment paradigms for the throwing athlete. The progression of evidence-based arm care has taken generations of innovators to get to where we are today. In 1983, Dr. Frank Jobe pioneered the original EMG study on the deltoids, subscapularis and what they referred to as the "SIT" muscles (supraspinatus, infraspinatus, and teres minor) during the pitching motion. 1 This work continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In an effort to reduce the occurrence of these injuries, coaches have introduced arm care programs focused on enhancing muscle and joint strength, dynamic stability, and range of motion (ROM) [5]. These programs aim to address musculoskeletal injury risk factors and promote injury prevention among players [4,6]. Nonetheless, these arm care programs often lack specificity since coaches without access to an athletic trainer or physical therapist (PT) find it challenging to identify individual injury risk factors for each player [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to reduce the occurrence of these injuries, coaches have introduced arm care programs focused on enhancing muscle and joint strength, dynamic stability, and range of motion (ROM) [5]. These programs aim to address musculoskeletal injury risk factors and promote injury prevention among players [4,6]. Nonetheless, these arm care programs often lack specificity since coaches without access to an athletic trainer or physical therapist (PT) find it challenging to identify individual injury risk factors for each player [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…These exercises were included in the Evidence Based Arm Care program previously published with links to exercise videos. 25 Randomization was done by pulling a card out of an opaque envelope with the exercise written on the chosen card to be done first. Wrist ulnar deviation was performed by the subject holding the resistance band with elbows extended, palms facing down, and arms held at shoulder height.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been observed that decrease mean hamstring flexibility has been found in KOA ( Onigbinde et al, 2013 ). This decreased flexibility may increase the compressive stress on the patello-femoral joint and lead to patellofemoral syndrome, which often contributes to osteoarthritis and can result in pain and limitations in physical functioning ( Jyoti & Yadav, 2019 ; Mahant & Shukla, 2021 ; Mullaney & Fukunaga, 2016 ; Onigbinde et al, 2013 ; Sherazi et al, 2022 ; Walli, McCay & Tiu, 2023 ).…”
Section: Introductionmentioning
confidence: 99%